2012
DOI: 10.1111/j.1348-0421.2012.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of swine influenza viruses isolated in Japan between 2009 and 2012

Abstract: Eleven swine influenza viruses (SIVs) isolated from pigs in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The results of serologic examination (Goto et al., ) and of virus isolation from swabs taken at slaughterhouses (T. Saito, S. Kasuo, Y. Yamashita, K. Goto, H. Kubo, unpublished data) confirmed that H3N2 viruses of human lineage have occasionally entered Japanese pig populations. After the emergence of the H1N1pdm09 virus in humans, the virus infected pig populations in Japan and reassorted with H1N2 IAV (Matsuu et al., ).…”
Section: Influenza Viruses Identified In Asian Swine Populationsmentioning
confidence: 99%
“…The results of serologic examination (Goto et al., ) and of virus isolation from swabs taken at slaughterhouses (T. Saito, S. Kasuo, Y. Yamashita, K. Goto, H. Kubo, unpublished data) confirmed that H3N2 viruses of human lineage have occasionally entered Japanese pig populations. After the emergence of the H1N1pdm09 virus in humans, the virus infected pig populations in Japan and reassorted with H1N2 IAV (Matsuu et al., ).…”
Section: Influenza Viruses Identified In Asian Swine Populationsmentioning
confidence: 99%
“…It is, therefore, necessary to isolate and characterize SIVs circulating in each region in a timely manner to understand the global status of SIVs. In Japan, SIVs belonging to the A(H1N1)pdm09, classical swine H1N2 virus and human seasonal virus‐derived H3N2 virus lineages have been isolated from 2009 to 2013 (Matsuu et al., ; Ozawa et al., ). Here, we genetically characterized 24 SIV strains isolated in Japan together with recent global SIV and human isolates.…”
Section: Introductionmentioning
confidence: 99%
“…However, genetically and antigenically distinct virus lineages have been individually established in North America, Asia, and Europe (11) likely due to the limited intercontinental transport of pigs, unlike those of humans or wild aquatic birds. In Japan, SIVs of A(H1N1)pdm09 virus-derived H1N1, the so-called "classical swine virus lineagederived H1N2" and North American "triple reassortant" H3N2 subtypes have been isolated recently (12), although the last H3N2 virus was isolated from a pig imported from Canada during animal quarantine and is not considered a circulating strain in Japan. Thus, SIV surveillance should be conducted in all regions and on a regular basis.…”
mentioning
confidence: 99%